Treasury finance and development banking : a guide to credit, debt, and risk - Mazzi, Biagio (Hoboken, New Jersey : John Wiley & Sons, 2013)
This book analyzes credit from the beginning--the point at which a borrowing entity decides to raise capital through its treasury operation. The author delves into the crucial functions that treasury funding plays in the operations of financial institutions, governments, and corporations. More importantly, he clearly demonstrates the various ways that treasury funding affects how financial activities are assessed, transactions are priced, and financial risks are managed.
Includes bibliographical references (pages 283-287) and index.
oif 15/06/15
Loan
Keywords: Credit; Bank loans; Debt; Financial risk; Development banks